Economic model of sport non profit making organization - Miloš Kosík; Miroslav Pacut (Palacký University Olomouc, 2010)
Sport involves multifunctional social phenomenon. There is relationship to other areas of social activities in sport. In our report we focused on relation between sport and economics, specially financing sports clubs. These financial resources touch on non profit making organization and they down in Andreff´s models. Further follow-up model is economic model of non profit making organization. That model expands information about incomes of sports clubs in Czech Republic. We suppose that differenciations of financing exist at sport clubs in Czech Republic and in abroad. They do not concern about club size but about legal form. The goal of this article is chracteristic and comparision. The goal was done by using the methods of documents working, analyse, synthesis and comparision.